2005
DOI: 10.1007/s10877-005-1655-0
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Near-Infrared Spectroscopy in People With Dark Skin Pigmentation

Abstract: In patients with a dark pigmented skin, NIRS StO2 measurements should be interpreted with caution, as melanin clearly interferes with the quality of the reflected NIRS signal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 23 publications
1
80
0
Order By: Relevance
“…Reasons for the observed failure to obtain sufficient signal may be hair color as well as dark skin pigmentation in one of the subjects. It is further known that there are still unsolved inter-individual anatomical and/or physiological differences occurring in NIRS which may lead to failure of sufficient signal (Hiroki et al, 2005, Wassenaar andVan den Brand, 2005).…”
Section: Subjectsmentioning
confidence: 99%
“…Reasons for the observed failure to obtain sufficient signal may be hair color as well as dark skin pigmentation in one of the subjects. It is further known that there are still unsolved inter-individual anatomical and/or physiological differences occurring in NIRS which may lead to failure of sufficient signal (Hiroki et al, 2005, Wassenaar andVan den Brand, 2005).…”
Section: Subjectsmentioning
confidence: 99%
“…Near-infrared spectroscopy relies on the principle that light, at a wavelength 650 -1000 nm, passes readily through skin and subcutaneous tissue however is absorbed by chromophores such as Hb, cytochrome oxidase and melanin 73 . Given this phenomenon, it would seem that the degree of skin pigmentation would have a significant effect on the reported rSO 2 value, in that the darker and more pigmented the skin, the more the NIRS signal would be impeded.…”
Section: Discussionmentioning
confidence: 99%
“…Given this phenomenon, it would seem that the degree of skin pigmentation would have a significant effect on the reported rSO 2 value, in that the darker and more pigmented the skin, the more the NIRS signal would be impeded. Wassenaar et al (2005) reported a loss of signal when using NIRS on human patients with very dark skin; however the sample size was deemed too small to quantify the effect 73 . Alternatively, in a study performed on calf skulls, no significant difference in NIRS signal was observed when the probe was placed over black or white skin, nor was there a detectable difference in rSO 2 values when the skin was removed from the skull 74 .…”
Section: Discussionmentioning
confidence: 99%
“…In patients with dark skin pigmentation, the blood oxygen saturation should be interpreted with caution, as melanin clearly interferes with the quality of the reflected NIRS signal. 9 For emulating the effect, India Ink is applied as an absorber to control the phantom tissue' absorption coefficient. In addition, gelatine is chosen as the coagulator to simulate tumor tissue.…”
Section: Experiments and Analysismentioning
confidence: 99%
“…As skin color is also determined by the presence of chromophores, it is plausible that NIRS signal quality may be affected by dark skin pigmentation. 9 Considering this phenomenon, a phantom experiment is implemented, which use Intralipid and India Ink to simulate the absorbance and scattering of NIRS light respectively. The experimental result shows that the proposed device is able to measure the absorption coefficients of the phantom tissue and the blood oxygen saturation, so that the concerned canceration case can be detected.…”
Section: Introductionmentioning
confidence: 99%